Pengaruh Asuhan Kefarmasian Terhadap Outcome Klinis Dan Kualitas Hidup Pada Pasien Diabetes Melitus Tipe 2 - Khairunnisa; Rawitri, Kiki; Wiryanto; Wahyuni, Sri (Pengurus Pusat Ikatan Apoteker Indonesia, 2021)
The role of pharmacists in pharmaceutical care has been shown to improve therapeutic outcomes in patients with diabetes mellitus (DM) in various countries. This study aims to implementation of pharmaceutical care and determine its impact on clinical outcomes and quality of life of type 2 DM patients at the community pharmacies. This study used a comparative experimental method with a prospective cohort study design before and after intervention on 38 types 2 DM patients who met the inclusion criteria at one of the community pharmacies in Medan city in August-December 2020. Clinical outcome data included random blood glucose (RBG) levels and HbA1c values ​​were obtained from direct examination of the patient, and quality of life data was obtained using the EQ-5D-3L questionnaire. The data were analyzed using the Wilcoxon Signed-Rank test and the Friedman test in the SPSS V22.0. program The results showed that the mean RBG value before the intervention was 278.58 ± 75.278 mg/dl and after the intervention, there was a decrease of 179.68 ± 14.008 mg/dl (α<0.05), the HbA1c value was 9.021 ± 1.029% to 8.368 ± 1.049% (α<0.05). There was a significant increase in the average quality of life index before the intervention from 0.849 ± 0.1266 and after the intervention to 0.967 ± 0.0657 (α <0.05). Based on the results of the study, it was concluded that the implementation of pharmaceutical care had an impact on improving clinical outcomes and quality of life in type 2 DM patients at community pharmacy